PENGEMBANGAN MATERI AJAR KETERAMPILAN BERBAHASA JAWA RESEPTIF BERBASIS UNGKAPAN TRADISIONAL SEBAGAI MEDIA PENDIDIKAN KARAKTER - Utami, Esti Sudi; Supriyanto, Teguh (LITERA, 2015)
Abstract This study aims to develop traditional-expression-based learning materials for Javanese receptive skills as character education media for junior high school (JHS) students. This was a research and development study. The research product was a model of learning materials relevant to Javanese learning needs at JHS. The developed learning materials were in the form of story discourses entitled proverbs containing character values. The learning materials were packed in an anthology of short stories and a short movie CD using Javanese of the ngapak [a], Surakarta [í»], dan Pati [ m] dialects. The learning materials for the [a] dialect were used at JHSs in the areas around Kebumen and Pekalongan. Those for the [í»] dialect were used in the areas around Surakarta, Salatiga, and Semarang. Those for the [ m] dialect were used in the areas around Pati and Blora. The results of the product evaluation showed that the products were good with scores of 4.35 for the book and 4.50 for the short movie CD. The model of the materials could be used as media to improve receptive skills and inculcate values through character education into students.